Education For Indonesian Citizens: From Good Citizens to Active Citizens - Venna Puspita Sari; Suryaningsi Suryaningsi (Pelopor Publikasi Akademika, 2023)
This paper emphasizes the imperative for Indonesia to shift from passive good citizens to active citizens in order to confront the nation's multifaceted challenges. Active citizenship is pivotal for promoting good governance, combatting corruption, advancing social justice, and fortifying democracy. To realize this transition, collaboration between the government, civil society organizations, and educational institutions is crucial. Civic education is identified as a critical tool for nurturing active citizens, with schools playing a vital role in imparting knowledge about rights, responsibilities, critical thinking, civic participation, and social responsibility. The Pancasila learner profile and the active citizen framework are proposed as interconnected concepts that can shape students' character and behavior while endorsing social justice. However, this transformation faces complexities including political illiteracy, elite influence, and educational inadequacies. Resolving these challenges demands concerted efforts and resource allocation. The government's commitment to civic education, enhancement of educational quality, provision of a free and impartial media platform, and encouragement of active citizenship are deemed imperative for fostering an engaged and participatory citizenry that contributes positively to Indonesia's societal progress.